Correlative Light and Scanning Electron Microscopy for Observing the Three-Dimensional Ultrastructure of Membranous Cell Organelles in Relation to Their Molecular Components. (December 2015) - Koga, Daisuke; Kusumi, Satoshi; Bochimoto, Hiroki; Watanabe, Tsuyoshi; Ushiki, Tatsuo
Although the osmium maceration method has been used to observe three-dimensional (3D) structures of membranous cell organelles with scanning electron microscopy (SEM), the use of osmium tetroxide for membrane fixation and the removal of cytosolic soluble proteins largely impairs the antigenicity of molecules in the specimens. In the present study, we developed a novel method to combine cryosectioning with the maceration method for correlative immunocytochemical analysis. We first immunocytochemically stained a semi-thin cryosection cut from a pituitary tissue block with a cryo-ultramicrotome, according to the Tokuyasu method, before preparing an osmium-macerated specimen from the remaining tissue block. Correlative microscopy was performed by observing the same area between the immunostained section and the adjacent face of the tissue block. Using this correlative method, we could accurately identify the gonadotropes of pituitary glands in various experimental conditions with SEM. At 4 weeks after castration, dilated cisternae of rough endoplasmic reticulum (RER) were distributed throughout the cytoplasm. On the other hand, an extremely dilated cisterna of the RER occupied the large region of the cytoplasm at 12 weeks after castration. This novel method has the potential to analyze the relationship between the distribution of functional molecules and the 3D ultrastructure in different composite tissues.